A new loss minimization approach for underground primary feeders - Pekiner, FO (IEEE, 1998)
As distribution system investment and energy costs continue to increase, more distribution engineers are attempting to evaluate loss calculations for the system. The optimization of underground primary feeder requires a proper approach of evaluating the cost of feeder losses. This paper derives an approach for the losses of underground primary feeder in urban areas. The present worth method is used to properly account for conditions of load growth, loss factor and energy cost inflation. The total cost equations of feeder to be used for long range planning are derived considering energy and demand cost components, in the developed approach, for a given voltage level, load, and annual growth rates of load, loss factor and energy costs, optimum cable size of a primary feeder can be obtained by the derived expressions. A sensitivity analysis is included to determine the effect of changing input values such as load growth, loss factor and energy cost.
Keywords: Automation & Control Systems; Computer Science; Engineering; Optics; Telecommunications